Pengelolaan Tpa Supit Urang Dengan Keterlibatan Sektor Informal - Rahajeng, Anggit Suko; Meidiana, Christia; Anggraeni, Mustika (Jurnal Tata Kota dan Daerah, 2014)
Supit Urang Landfill is located in Mulyorejo, District of Sukun, City of Malang. There are scavenging activity by 217 scavengers in Supit Urang Landfill but there has been no related with management’s activity of the scavengers. Without the scavenger’s management there are many violations that disturb the operational tools that interfere with landfill work and also endangering the scavengers. Recommendations of the involvement of scavengers in Supit Urang Landfill were formulated by evaluation of operating system, identification the benefit of scavengers activity and empowerment management‘s recommendation. The evaluation of operating system in Supit Urang Landfill by scoring analysis showed that the operational system is controlled landfill so scavenging activities is a legal activity. Identification contribution of scavenging activity by economic estimation based on cost and benefit showed that the scavengers in supit Urang reduced waste and operational cost by 1.9% and 1.26%. This activity also gave scavengers benefit up to 5.48 much bigger than scavenging cost. Empowerment management were formulated by location for scavengers and recommendation for empowerment’s factors that influence with scavengers in Supit Urang Landfill. Map’s overlay, counting of rits and operational times were used to choose location for scavengers. Locations for scavengers are in limited cultivation zone with a distance of 800 m from the active cell with 7.57 hour of waste travel time per day. Factors that influence the empowerment of scavengers at Supit Urang Landfill are institutional, home range and activity. Keywords: Scavengers, Controlled Landfill , Benefit Cost Ratio